Parenting style, emotional intelligence, and social anxiety among adolescents: a systematic literature review - Gao, Yang; Ismail, Nellie; Arshat, Zarinah; Dahamat Azam, Mohamad Naqiuddin (Human Resources Management Academic Research Society (HRMARS), 2024)
This review set out to synthesize and analyze the existing research on the relation between parenting style, emotional intelligence (EI) and social anxiety among adolescents. An extensive and systematic search across multiple databases such as Google Scholar, Science Direct, and Web of Science was performed. The keywords related to parenting styles, EI, and social anxiety were employed, resulting in the initial retrieval of over 90,000 articles. This paper focus on studies involving participants aged 10-18, with a particular emphasis on EI or social anxiety as outcome variables and parenting style as a predictor. Ultimately, 27 papers met the study requirements and were subjected to a critical appraisal examining the clarity of research questions, sample representativeness, research procedures, result analysis, and alignment with study objectives. The analysis revealed marked variation in the impact of parenting styles on EI across different cultural settings. Authoritative parenting consistently showed positive outcomes on adolescents' psychological flexibility and emotion regulation. In contrast, the authoritarian and indulgent/neglectful parenting styles were related to less adaptive behaviors regarding these domains. However, this association varied in non-Western contexts, with authoritarian parenting sometimes positively linked to EI. This critical evaluation of the parenting styles, with specific reference to EI and social anxiety, provides valuable insights into the intricate nature of adolescent development.